Satow's diplomatic practice - Roberts, Ivor , 1946- (United Kingdom : Oxford University Press, 2011)
The new edition of this classic work revises and examines the diplomatic practice of the last thirty years. It provides a comprehensive analysis of all areas of diplomacy, including its history, diplomatic immunities, and features new sections on international organisations and terrorism, making it an indispensable guide for anyone in the field
1. Diplomacy in general -- 2. Diplomatic relations -- 3. Diplomatic privileges and immunities -- 4. Diplomatic missions -- 5. Consular matters -- 6. International organizations -- 7. The peaceful settlement of international disputes and the development and role of international criminal tribunals -- 8. Alternative and non-state diplomacy -- 9. International transactions -- 10. Envoi
Includes bibliographical references (p. 705-712) and index
Keywords: Diplomacy; Diplomatic and consular service